2020
DOI: 10.1177/1550059420916634
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder Classification Based on Different Convolutional Neural Network Models: Deep Learning Approach

Abstract: The human brain is characterized by complex structural, functional connections that integrate unique cognitive characteristics. There is a fundamental hurdle for the evaluation of both structural and functional connections of the brain and the effects in the diagnosis and treatment of neurodegenerative diseases. Currently, there is no clinically specific diagnostic biomarker capable of confirming the diagnosis of major depressive disorder (MDD). Therefore, exploring translational biomarkers of mood di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 110 publications
1
51
1
Order By: Relevance
“…However, it is worth noting that recent reviews are specifically dedicated to this field of research [9], [157] and suggest that these approaches would be a useful methodology to implement in the MDD diagnosis process. As pointed out by some authors [158], [159], the use of both machine and deep learning techniques can provide valuable biomarkers in discriminating MDD from other mood disorders, and can also be adapted to the computer-aided diagnosis of depression. Overall, the present work has also some strengths.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that recent reviews are specifically dedicated to this field of research [9], [157] and suggest that these approaches would be a useful methodology to implement in the MDD diagnosis process. As pointed out by some authors [158], [159], the use of both machine and deep learning techniques can provide valuable biomarkers in discriminating MDD from other mood disorders, and can also be adapted to the computer-aided diagnosis of depression. Overall, the present work has also some strengths.…”
Section: Discussionmentioning
confidence: 99%
“…C. Uyulan et al [44] suggested three convolutional neural network-based models which were integrated with advanced computational neuroscience methodology named ResNet-50, MobileNet, and Inception-v3 to apply to the EEG recorded signals from both left and right hemispheres with eye closed states. The produced artifacts as a result of eye and muscle activities were removed by the wavelet transform method.…”
Section: Deep Learning Methods For Depression Detection Using Eeg Signalsmentioning
confidence: 99%
“…C. Uyulan et al [45] suggested three convolutional neural network-based models which integrated with advanced computational neuroscience methodology named ResNet-50, MobileNet, and Inception-v3 to apply to the EEG recorded signals from both left and right hemispheres with eye closed states. The produced artifacts as a result of eye and muscle activities were removed by the wavelet transform method.…”
Section: Deep Learning Methods For Depression Detection Using Eeg Signalsmentioning
confidence: 99%